Societal Expectation of Women in Cry, the Peacock by Anita Desai (International Journal of Scientific Research in Science and Technology, 2024)
This paper examines the societal expectations imposed on women in Anita Desai’s Cry, the Peacock and their psychological consequences on the protagonist, Maya. The novel presents a harrowing exploration of female oppression, emotional neglect, and patriarchal conditioning, all of which culminate in Maya’s mental deterioration. Women in traditional Indian society are expected to embody submission, patience, and self-sacrifice, often at the cost of their individuality and mental well-being. Through Maya’s experiences, Desai critiques these rigid gender norms and highlights the devastating effects of societal expectations on women’s identity, autonomy, and psychological health. This paper integrates feminist literary criticism, psychoanalytic theory, and cultural analysis to explore Maya’s struggle as a reflection of the broader oppression of women in patriarchal societies.